The Effect of Product Turnover on Company Performance of SMEs - Agus Sobar; Asep Deni; Riki Riswandi; Dendi Zainuddin Hamidi; Indra Permadi (Publindo Akademika, 2021)
Research related to the effect of product turnover on the performance of companies in the industrial sector is still needed to do research and study in depth. This is needed because the developed sector, especially related to product rotation, has an important role in advancing the sustainability of the company. The research methodology in this research is descriptive quantitative using simple linear regression analysis and using SPSS v 23 and Amos v 23 software as a calculation tool through a measurement model using simple Linear Regression at 87 MSMEs in Sukabumi City. The results of this study indicate a positive effect of product turnover on the performance of Small and Medium Enterprises.